Hydrographic survey using real time kinematic method for river deepening - Che Awang, Nor Aklima (Faculty of Geoinformation Science and Engineering, Universiti Teknologi Malaysia, 2011)
There is many surveys’s method in hydrographic surveying due to development of technologies. The latest development in technologies for example Global Positioning System (GPS) gives new challenges in surveying field. Surveyors use GPS technology for simple tasks or complex tasks. In hydrographic survey, the important data required are position, tidal reading and depth value. Normally, tidal reading is obtained at tidal station established near to survey area by using instrument like automatic or self-recording tide gauge. Depth of seabed is measured by using single beam or multi beam echo sounder without add up tidal value at the same time. The latest technique of getting position and depth simultaneously is by using RTK method